THE DEVELOPMENT OF TEACHING AND LEARNING ON THE GRAMMARTICAL STRUCTURE OF BOTH ACTIVE AND PASSIVE USING NEW RECOGNITION MODEL - Meteevorakij, Paveena (International Online Journal of Education and Teaching, 2023)
The research objectives of this study were 1) to develop teaching and learning about tense grammar structures, both active and passive, using a new model of recognition 2) to determine the effectiveness of the lessons on the active and passive tense grammar structure and 3) to compare the achievement of tense grammar structure both active and passive of the new teaching style developed with the traditional one. from students of Rajamangala University of Technology Tawan-ok Bangpra Campus. The population and sample were the students of Rajamangala University of Technology Tawan-ok Bangpra Campus using Z-test statistics in a comparative test of academic achievement on the active and passive tense grammar structure of the experimental group and control group. The findings resulted in a descriptive form or model that could be used in teaching about the subject grammar structure, both active and passive tenses that use new recognition-based learning. The result of the experimental group’s findings on the structure of tense grammar were both active and passive was equal to 80.07/82.34 , which is higher than the threshold set in the assumption, 80/80. Moreover, the results of the comparison of academic achievement on the active and passive tense grammar structure of the new teaching and learning model developed with the traditional one showed that the experimental group The average test score was 41.17, while the control group had an average of 38.79. When testing the difference between the mean values, there was a statistically significant difference in student achievement in the experimental group and the control group at a level of 0.05. It had higher average of test scores than the control group.